Kondisi dan Fenomena Pertumbuhan Ekonomi di Negara-Negara yang Tergabung di G20 - Rama Mukti Nautika; Didit Purnomo (Jurnal Mirai Management, 2023)
The G20 is a collection of countries that have the greatest monetary power in the world. The reason Indonesia joined the G20 is because currently Indonesia is ranked sixteenth based on GDP. In this way, Indonesia's position becomes equal between China and India, whose economic growth has always been above average in the world economic system. Meanwhile, other developed countries usually have dynamic tendencies. This research uses secondary data in the form of panel data. The findings show that labor, exports, imports and inflation have both simultaneous and partial effects on economic growth in countries that are members of the G20 during the 2017-2021 period Keywords: Economic Growth, Exports, Imports, Employment, Inflation